Abordaje diagnóstico del carcinoma medular de tiroides - Bohorquez Murillo, Karen Anabel (Machala : Universidad Técnica de Machala, 2021)
Introduction: Medullary thyroid carcinoma is a neoplasm derived from parafollicular cells or C cells, also known as solid carcinoma, C cell carcinoma or hyaline carcinoma, its mortality rate is 13.4% worldwide. Its prognosis is highly variable, since it depends on the stage in which it has been diagnosed, although it has an overall survival of 75 to 85% within 10 years of diagnosis. Objective: To establish the diagnostic approach for medullary thyroid carcinoma, through an updated bibliographic review of scientific articles, which generates updated knowledge on the subject. Methodology: This is a descriptive study, in which through an exhaustive search of bibliographic sources, an analysis and synthesis of various scientific articles collected from high-impact digital repositories such as PUBMED, COCHRANE, GOOGLE SCHOLAR and MEDSCAPE, of the last 5 years. Conclusion: Medullary thyroid cancer commonly presents asymptomatic and is detected mainly in the presence of a thyroid nodule regularly incidentally, this occurs through physical examination or radiological studies in search of another pathology. Its symptoms refer to hormonal hypersecretion compatible with endocrine syndromes. When associated with distant metastases, it can usually be localized to the liver, bone system, and respiratory system.
Introducción: El carcinoma medular de tiroides es una neoplasia que se deriva de células parafoliculares o células C, denominado también como carcinoma sólido, carcinoma de células C o carcinoma hialino, su tasa de mortalidad incide a un 13,4% a nivel mundial. Su pronóstico es muy variable, ya que depende del estadio en que ha sido diagnosticado, aunque tiene una supervivencia global del 75 a 85% en un lapso de 10 años a partir del diagnóstico. Objetivo: Establecer el abordaje diagnóstico del carcinoma medular de tiroides, mediante una revisión bibliográfica actualizada de artículos científicos, que genere conocimiento actualizado sobre la temática. Metodología: Se trata de un estudio descriptivo, en el cual mediante de la búsqueda exhaustiva de fuentes bibliográficas, una análisis y síntesis de diversos artículos científicos recopilados de repositorios digitales de alto impacto como PUBMED, COCHRANE, GOOGLE SCHOLAR y MEDSCAPE, de los últimos 5 años. Conclusión: El cáncer medular de tiroides comúnmente se presenta asintomático y es detectado principalmente ante la presencia de un nódulo tiroideo regularmente de forma incidentalmente, esto se da por medio del examen físico o estudios radiológicos en busca de otra patología. Su sintomatología hace referencia a la hipersecreción hormonal compatible con síndromes endocrinos. Cuando se asocia con metástasis a distancia, se puede localizar habitualmente en el hígado, sistema óseo y sistema respiratorio.
Keywords: CARCINOMA MEDULAR DE TIROIDES; CANCER DE TIROIDES; DIAGNOSTICO DE CARCINOMA MEDULAR